MRI Characterization of Non-traumatic Intracerebral Hemorrhage in Young Adults - Elmegiri, Mohamed; Koivunen, Riku-Jaakko; Tatlisumak, Turgut; Putaala, Jukka; Martola, Juha (Frontiers in Neurology, 2020)
Background and purpose: Non-traumatic intracerebral hemorrhage (ICH) in younger population is a relatively rare event but is associated with considerable mortality and poor functional outcome. Imaging plays a crucial role in determining the underlying cause and guide treatment of ICH. In up to 41% of patients in prior studies the underlying cause remained elusive. However, the usage of MRI as part of diagnostic work-up was scanty. We aimed to analyze MRI findings of young ICH patients and assess specificity and sensitivity of MRI in detecting structural or local underlying causes of ICH. Methods: We included patients aged 15-49 years with first-ever ICH identified from a prospective hospital discharge registry, 2000-2010. All study patients underwent MRI imaging within 3 months of ICH. Imaging data was analyzed by a senior neuroradiologist blinded to clinical data. We calculated the diagnostic accuracy of MRI in detecting structural/local underlying causes. Results: Of our 116 patients (median age 39; 67% males), structural/local causes were the leading causes of ICH (50.0%) and of these, bleeding cavernomas (23.3%) were the most frequent followed by arteriovenous malformations (12.9%), CVT (7.8%), brain tumors (5.2%), and moyamoya disease (0.9%). Lobar location of ICH was more prevalent in younger patients. MRI was highly sensitive (90.0%, 95% confidence interval 79.5 - 96.2%) for detection of structural/local causes compared to angiographic imaging (55.6%, 95% CI 40.0 - 70.4%), while MRI was less specific (87.3%, 95% CI 75.5 - 94.7%) for structural/local causes, compared to angiographic imaging (97.4%, 95% CI 86.5 - 99.9%). Conclusion: MRI was highly sensitive for the detection of structural and local causes underlying ICH in young adults. Thus, MRI should be considered in the diagnostic work-up of all young ICH patients to enable targeted secondary prevention.